Input Energy Price Volatility and Profitability in Vietnam’s Steel Industry: A Panel Data Approach - Thi, Tho Do; Gia, Khuong Dinh; Hoang, Hai Nguyen (International Journal of Energy Economics and Policy, 2025)
The steel manufacturing industry is one of the most energy-intensive sectors, making it highly sensitive to input cost fluctuations, especially raw material and energy prices. This study investigates the impact of key input price volatility - including iron ore, coking coal, and fuel oil - on the profitability of listed steel companies in Vietnam between 2019 and 2024. Using panel data of ten publicly traded firms and applying robust estimation techniques including Pooled OLS, Fixed Effects, and Feasible Generalized Least Squares (FGLS), the study evaluates how variations in input costs affect return on equity (ROE), a proxy for financial performance. The empirical results reveal that rising prices of coking coal and fuel oil have a significantly negative effect on profitability, whereas fluctuations in iron ore prices exhibit a more complex and less consistent impact. Additional control variables such as exchange rate and financial leverage also contribute to profitability volatility. The findings underscore the vulnerability of energy-dependent industrial sectors in emerging markets to raw material cost shocks, particularly under global supply disruptions and geopolitical tensions. This paper provides policy implications for risk mitigation, suggesting that firms in the steel sector should adopt hedging strategies and diversify energy sources, while national policymakers should consider strategic stockpiling and tax incentives to stabilize energy input costs. The results also add to the literature on energy price transmission and profitability under uncertainty in transitional economies.